Pencegahan Bahaya Anti Narkoba pada Generasi Muda : Growth with Healthy Mindset Without Drugs - Suheriah Mulia Devi; Angga Dwi Pramudika; Angelica Eugini Virgie (Nuras : Jurnal Pengabdian Kepada Masyarakat, 2026)
The problem of drug abuse among adolescents poses a serious threat to the sustainability of human resource quality, especially in strategic areas such as Nenang Village, Penajam Paser Utara Regency. This community service activity aims to increase awareness and mental resilience among 8th-grade students of SMPN 10 Penajam Paser Utara through a socialization program entitled "Growth with a Healthy Mindset Without Drugs." The method used was an educational-participatory approach involving Anti-Drug Ambassadors as peer resource persons through interactive lectures, guided discussions, and assertive communication simulations. The results of the activity showed a significant increase in students' knowledge regarding the neurobiological dangers of addictive substances, as well as the legal consequences under Law Number 35 of 2009. In addition to increased knowledge, this activity also encouraged changes in students' attitudes and skills, demonstrated by their ability to confidently practice techniques for resisting peer pressure as a form of preventive behavior against drug abuse. The presentation of certificates to the school symbolizes the program's ongoing commitment to strengthening anti-drug attitudes in the educational environment.